Coincidence of Concentric Vessel-Wall Contrast Enhancement in Moyamoya Disease and Acute Postoperative Ischemic Stroke During Revascularization Procedures - Patrick Haas; Till-Karsten Hauser; Lucas Moritz Wiggenhauser; Leonie Zerweck; Marcos Tatagiba; Nadia Khan; Constantin Roder (Brain Sciences, 2024)
Background: Concentric vessel-wall contrast enhancement (VW-CE) of the terminal carotid artery and its proximal branches may be linked to ischemic strokes, disease activity and progression in Moyamoya disease (MMD). The objective of this retrospective cohort study is to analyze the association between VW-CE and perioperative acute ischemic stroke (PAIS) occurring within 24 h after revascularization. Methods: All previously untreated MMD patients who required revascularization and who had undergone preoperative MRI with VW-CE-sequences were included. PAIS was detected by CT and/or diffusion-weighted MRI sequences within 24 h postoperatively. Results: Of the 110 patients included (female-to-male ratio: 2.7:1, median age: 45.1 (16.6–69.2); n = 247 revascularizations), a priori VW-CE was present in 67.3% (mean time from MRI to first surgery: 86 days ± 82 days). PAIS occurred in five patients undergoing primary revascularization (PAIS rate per revascularization: 2.1%), all of whom had a preoperative pathological VW-CE in the vascular segment corresponding to the stroke area. Two (40%) incidents of PAIS occurred in revascularized territory, while three (60%) occurred in non-revascularized vascular territory. In each case, the supplying artery exhibited VW-CE, indicating disease activity. No additional PAIS occurred during subsequent revascularizations in cases of multistage procedures (n = 38), such as ACA or PCA revascularization as a second step. Conclusions: Preoperative VW-CE in one or more vascular segments may be a marker for postoperative stroke in the respective vascular territory at the time of revascularization. VW-CE imaging should be routinely performed when planning revascularization in MMD. If VW-CE is found, strict perioperative monitoring of these high-risk patients should be performed to achieve the best results possible.